1988
DOI: 10.1007/bf02542409
|View full text |Cite
|
Sign up to set email alerts
|

A convenient synthesis of long‐chain 1‐O‐Alkyl glyceryl ethers

Abstract: A convenient and economical procedure for synthesis of long‐chain 1‐O‐alkyl glyceryl ethers (V) is described. Alkyl glycidyl ethers (II) which were derived from the reaction of alcohols (I) with epichlorohydrin using a phase transfer catalyst were first converted into the corresponding dioxolanes (III) or 1‐O‐alkyl‐2,3‐di‐O‐acetylglycerols (IV). Subsequent hydrolysis of the resultant products provided 1‐O‐alkyl glyceryl ethers (V) in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…More recently, Urata et al (1988) have achieved the synthesis of 1-O-alkylglycerols via prior preparation of alkyl glycidyl ethers (1-O-alkyl-2,3-epoxypropanes), by coupling epichlorohydrin with fatty alcohols using a quaternary ammonium salt as phase transfer catalyst in an alkaline water-hexane solvent system, resulting in 80% yield for the oleyl chain. The epoxide was then converted to the corresponding acetonide or diacetate by treatment with acetone and boron trifluoride etherate (BF 3 ·Et 2 O) or acetic acid anhydride with a tertiary amine, followed by hydrolysis, in 63 and 67% overall yields, respectively.…”
Section: Chemical Synthesismentioning
confidence: 99%
“…More recently, Urata et al (1988) have achieved the synthesis of 1-O-alkylglycerols via prior preparation of alkyl glycidyl ethers (1-O-alkyl-2,3-epoxypropanes), by coupling epichlorohydrin with fatty alcohols using a quaternary ammonium salt as phase transfer catalyst in an alkaline water-hexane solvent system, resulting in 80% yield for the oleyl chain. The epoxide was then converted to the corresponding acetonide or diacetate by treatment with acetone and boron trifluoride etherate (BF 3 ·Et 2 O) or acetic acid anhydride with a tertiary amine, followed by hydrolysis, in 63 and 67% overall yields, respectively.…”
Section: Chemical Synthesismentioning
confidence: 99%
“…A transesterification reaction 15 using 1,3-propanediol in CHCl3 promoted the cleavage of five-membered ring boronates (7, 8, 9) furnishing after flash chromatography purification the desired natural products chimyl (1), batyl (2) and selachyl (3) alcohols in 87%, 85%, 77% yields. (Scheme 1) Compared to other procedures described in the present literature [13,16,17,18,19,20,21,22] the synthesis of chimyl (1), batyl (2) and selachyl (3) alcohols described herein is an efficient synthetic approach, which presents a straightforward chemical transformation of an epoxide function to cyclic phenylboronate intermediates.…”
Section: IIImentioning
confidence: 99%
“…Another synthetic target molecule is an important intracellular signaling molecule. L-α-Phosphatidyl-D-myo-inositol-3,4,5-triphosphate[PtIns (3,4,5)p 3 ] is an in vivo product of phosphoinositide 3-OH-kinase (PI3K) and was first isolated by Traynor-Kaplan et al (48) from agonist-stimulated human neutrophils in 1988. Certain studies have suggested that PtIns(3,4,5)P 3 and PI3K are both involved in a new intracelullar signaling system independent of the PtIns(4,5)P 2 -based pathway (Scheme 17).…”
Section: Scheme 11mentioning
confidence: 99%
“…To this end, we have previously reported on the industrial scale preparation of alkyl glyceryl ethers, pseudoceramides, and related compounds through the combination of protecting groups and the phase-transfer catalytic (PTC) reaction, as shown in Scheme 1 (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%